1981
DOI: 10.4141/cjas81-026
|View full text |Cite
|
Sign up to set email alerts
|

NUTRITIVE VALUE OF LEAF PROTEIN CONCENTRATES PREPARED FROM Amaranthus SPECIES

Abstract: Amaranthus . Their proximate composition and phenolic content were determined. In vitro nitrogen digestibility was low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The toxic substance(s) in amaranth have not yet been conclusively identified. Cheeke and Bronson (1980) and Cheeke et al (1981) suggest that saponins and phenolic compounds in the grain were the likely cause of the growth depression.…”
Section: Resultsmentioning
confidence: 96%
“…The toxic substance(s) in amaranth have not yet been conclusively identified. Cheeke and Bronson (1980) and Cheeke et al (1981) suggest that saponins and phenolic compounds in the grain were the likely cause of the growth depression.…”
Section: Resultsmentioning
confidence: 96%
“…Table 2 compares rat growth and feed intake on diets containing different Amaranthus leaf protein concentfates with those containing alfalfa. The poor growth rate of rats fed Amaranthus leaf protein concentrates (Table 2; Cheeke, Carlsson & Kohler, 1981) could be attributed to phenolic content, saponins, oxalates and high ash content. A , 1980).…”
mentioning
confidence: 99%
“…Concentrates extracted from the thin leaves of winged bean have been found to be of high nutritional value. Cheeke et al (1980) compared winged bean leaf concentrate with concentrates extracted from leaves of seven common tropical legume species and found that the winged bean concentrate had a protein efficiency ratio when fed to rats, second in value only to Clitoria ternata L. Kailasapathy and Sandrasegaram (1983) reported that concentrates extracted from winged bean leaves contained on a dry weight basis 59.7% crude protein, 5.13% crude fibre, 10.41% ash and 0.71% crude fat. The leaf concentrate contained a modest level of trypsin inhibitor activity that could be deactivated by heat treatment for twenty minutes.…”
Section: A Benign Nitrogen-rich Cover Cropmentioning
confidence: 99%